O evento 11 de setembro: (re)criação da história no romance Extremely Loud & Incredibly Close (2005), de Jonathan Safran Foer - Vani, João Paulo [UNESP] (2014)
This thesis investigates the narrative strategies used by Jonathan Safran Foer in Extremely Loud & Incredibly Close (2005) in order to verify how the author evaluates the episode of the terrorist attacks of 9/11. The tragedy is the beginning of a new period in the history of the United States and has been the subject of publications in several fields. This study examines, through the journey taken by the nine-year-old boy Oskar, whose father was a victim of the 9/11 attacks, how the events of the past are transformed into relevant historical facts, systems that allow the treatment of History through multiple perspectives, and the presence of trauma as a conection between History and Literature. Primarily focusing on the narrator, little Oskar, the analysis will pursue his journey in New York looking for answers to the death of his father on that catastrophic day, treated by Oskar as “the worst day”. The use of images, blanks, written with overlapping and dialogue with technology and coded messages such as SMS, which are present in the novel, will also be analyzed. The theoretical basis of this discussion includes texts by McHale (1992), Lyotard (1990), Jameson (2007), Santiago (2002), Connor (2000), White (1994), Le Goff (2003) and Hutcheon (1991)